Novel Molecular Detection of BPV-10 and BPV-11 Genotypes in Al- Anbar, and Baghdad Provinces - Mohammed A. Hamad1 , Murtadha A. Al-Mudhafr2 , Ahmed Majeed Al-Shammari3, Ahmed J. Neamah4 (Institute of Medico-legal Publications Pvt Ltd, 2021)
In this study, the prevalence of diverse bovine papilloma viruses in cutaneous lesions was investigated in Iraqicows. Fourteen specimens were taken from udder growths of Iraqi dairy cows, which demonstrated rice grain-likeand small, raised flesh-like appearance. DNA was extracted from the teat wart samples, then was amplified by thepolymerase chain reaction (PCR) using primers against BPV-10 (403 bp) and BPV-11 (560 bp). PCR results revealedmixed infections of BPV-10 and BPV -11 in four samples, while the remaining ten samples were infected with BPV10 only. These findings demonstrate the presence of bovine papillomaviruses 10 and 11 in rice grain-like cutaneouslesions on the teats of cows and multiple elevated growths on udder. The detection and report of the BPV-10 andBPV -11 genotypes in the current study is for first time in Iraq, which are known in the Middle East region, are crucialfor disease control measurements.